2014
DOI: 10.1117/12.2059595
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Bragg grating sensors for steel wire monitoring in real-time

Abstract: Steel wires are widely applied in industrial applications - in most cases as critical components fulfilling high safety requirements in harsh environments (e.g. dockside cranes). In this paper a technique for real-time monitoring of steel ropes applying optical strain sensors based on fiber Bragg gratings is presented. The optical sensors are integrated within the wire strand and replace the core. The strain transmission from the outer wires to the sensors is assured by the mechanical coupling between the opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…(2) For each pixel p ∈ IM gray , calculate mRTV by equations (10) and (11) and the total range △ðΩ p Þ in formulation (10).…”
Section: Infrared Imagementioning
confidence: 99%
See 1 more Smart Citation
“…(2) For each pixel p ∈ IM gray , calculate mRTV by equations (10) and (11) and the total range △ðΩ p Þ in formulation (10).…”
Section: Infrared Imagementioning
confidence: 99%
“…At present, the NDT methods of wire rope include electromagnetic [3,4], X-ray [5], acoustic [6][7][8][9], and optical [10] method [1]. X-ray apparatus has radioactive contamination; acoustic method detects wire rope by striking, which is simple but one-sided; CCD camera optical testing method can directly show the real defects through imaging, but it is susceptible to oil pollution; because of high sensitivity, high speed, and low cost, electromagnetic NDT method is widely used [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…This device essentially consists of an array of optical transmission filters integrated on a planar waveguide and permits a fast and simultaneous interrogation of multiple FBG sensors without any mechanically moving parts 10 . The present authors previously published an essay including theoretical and experimental study of the proposed device for the interrogation of FBG sensors 11 and demonstrated its promising features for the application of steel wire monitoring 12 . The purpose of this paper is to present the interrogation options of the proposed interrogator unit based on AWG chips.…”
Section: Introductionmentioning
confidence: 99%